2013
DOI: 10.12816/0000597
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Metabolism in a Sample of Egyptian Hypertensive Patients with Normal Kidney Function

Abstract: Background: Hyperuricemia is commonly associated with hypertension. Also, it is well known to coincide with the metabolic syndrome but is still not recognized as a risk factor. So, we aimed to evaluate hyperuricemia among a sample of hypertensive Egyptians with normal renal function. Methods: this study was performed on 303 hypertensive patients aged 30-69 years. Patients were divided into 2 groups according to the level of uric acid: group 1 composed of 168 hypertensive hyperuricemic patient sand group2 compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Previous researchers had similar observations. [4][5][6][7][8][9]29 Among the hypertensive subjects of the current study, those with stage II HTN had significantly higher uric acid than those with stage I HTN. The higher uric acid levels with higher stages of HTN were also described by Neki et al, and Meti et al 8,19 Moreover, both the systolic and diastolic BP had significant positive correlations with serum uric acid levels in the hypertensive subjects of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researchers had similar observations. [4][5][6][7][8][9]29 Among the hypertensive subjects of the current study, those with stage II HTN had significantly higher uric acid than those with stage I HTN. The higher uric acid levels with higher stages of HTN were also described by Neki et al, and Meti et al 8,19 Moreover, both the systolic and diastolic BP had significant positive correlations with serum uric acid levels in the hypertensive subjects of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, Bauer et al reported 31% of subjects with essential HTN to have hyperuricemia; the frequency was 55.4% in Egypt, 37.4% in Pakistan, 28.8% in Nepal, and two studies from India reported 37% and 46% hypertensive subjects to have hyperuricemia. [4][5][6][7][8][9] In a previous study in Bangladesh, the observed prevalence of hyperuricemia in hypertensive and normotensive subjects were 25.4% and 9.8%, respectively. 29 In the present study, hyperuricemia was observed in 29.7% of hypertensive patients and 6.0% of normotensive controls, which was similar to most of the studies dine in this part of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired renal uric acid clearance occurs before a decrease in glomerular filtration rate (GFR), so uric acid must be measured in all cases of hypertension together with BMI, total cholesterol, triglycerides and care must be taken to avoid the occurrence of metabolic complications. 14…”
Section: The Relationship Between Uric Acid and Hypertensionmentioning
confidence: 99%